Emotional Integration and Spiritual Formation: Integrating Emotion Into Formation of the Spirit - Erbe, Ryan G. (2025)
A recent special section of The Journal of Spiritual Formation and Soul Care initiated the conversation between psychologists and theologians about the role of emotions in the Christian life. While this special section accomplished its purpose, more remains to be said about emotions and spiritual formation. The current manuscript intends to continue the dialogue by discussing a type of emotion regulation known as Emotional Integration (EI). EI was recently introduced into psychological literature as a form of emotion regulation involving an accepting and interested stance toward one’s emotional experiences as a means of integrating emotion into central aspects of the self, including core values and goals. Initial empirical evidence demonstrating EI’s ability to enhance moral character, interpersonal relationships, and well-being will be highlighted. Evidence of EI in the nature of God, the character of Christ, and Psalm 42 will be reviewed along with implications for Christian ministers, teachers, and counselors.
Keywords: character formation; emotional integration; Emotion regulation; Self-determination theory; Spiritual Formation